The dynamics of regions and networks in industrial ecosystems - Ruth, Matthias; Davidsdottir, Brynhildur; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2009)
Industrial ecology provides a rigorous and comprehensive description of human production and consumption processes in the larger context of environmental and socioeconomic change. This volume offers methodologies for such descriptions, with contributions covering both basic and advanced analytical concepts and tools to explore the dynamics of industrial ecosystems, concentrating specifically on regions and networks.
The dynamics of regions and networks in industrial ecosystems : background and concepts / Matthias Ruth and Brynhildur Davidsdottir -- Dynamics of geographically based industrial ecosytems / Marian R. Chertow -- Regional dynamics and industrial ecosystems : an introduction / David L. Rigby -- Spatial and temporal life cycle assessment : ozone formation potential from natural gas use in a typical residential building in Pittsburgh, USA / Shannon M. Lloyd and Robert Ries -- Estimating generalized regional input-output systems : a case study of Australia / Blanca Gallego and Manfred Lenzen -- The economic and environmental consequences of reduced air transport services in Pennsylvania : a regional input-output life cycle assessment case study / Gyorgyi Cicas, Chris T. Hendrickson and H. Scott Matthews -- Design approach frameworks, regional metabolism and scenarios for sustainability / Tim Baynes, Jim West and Graham M. Turner -- Learning and evolution in industrial ecosystems : an introduction / Peter M. Allen -- A framework for analysis of industrial networks / Ruud Kempener ... [et al.] -- Understanding and shaping the evolution of sustainable large-scale socio-technical systems / Igor Nikolic, Gerard P.J. Dijkema and Koen H. van Dam -- Futures scenarios of industrial ecosystems : a research design for transportation planning / Paul Beavis ... [et al.] -- PowerPlay : developing strategies to promote energy efficiency / Matthias Ruth ... [et al.] -- The dynamics of regions and networks in industrial ecosystems : retrospect and prospect / Brynhildur Davidsdottir and Matthias Ruth.
Includes bibliographical references and index.
Keywords: Industrial location; Business networks; Industrial productivity; Environmental economics -- Case studies; Environmental economics -- Mathematical models; Electronic books